The effect of memantine, an antagonist of the NMDA glutamate receptor, in in vitro and in vivo infections by Trypanosoma cruzi. - Higo Fernando Santos Souza; Sandra Carla Rocha; Flávia Silva Damasceno; Ludmila Nakamura Rapado; Elisabeth Mieko Furusho Pral; Claudio Romero Farias Marinho; Ariel Mariano Silber (Public Library of Science (PLoS), 2019)
Chagas disease, caused by Trypanosoma cruzi, is a neglected tropical disease that affects 5-6 million people in endemic areas of the Americas. Presently, chemotherapy relies on two compounds that were proposed as trypanocidal drugs four decades ago: nifurtimox and benznidazole. Both drugs are able to eliminate parasitemia and to avoid seroconversion in infected people when used in the acute phase; however, their use in the chronic phase (the time when the majority of cases are diagnosed) is limited due to their serious side effects. Memantine is a glutamate receptor antagonist in the central nervous system of mammals that has been used for the treatment of Alzheimer's disease. Our group previously reported memantine as a trypanocidal drug that is able to induce apoptosis-like death in T. cruzi. In the present work, we further investigated the effects of memantine on the infection of RAW 264.7 macrophages and in vivo (in BALB/c mice). Here, we showed that memantine is able to diminish NO and Ca2+ entry in both LPS-activated and non-activated cells. These results, together with the fact that memantine was also able to reduce the infection of macrophages, led us to propose that this drug is able to activate a pro-oxidant non-NO-dependent cell defense mechanism. Finally, infected mice that were treated with memantine had diminished parasitemia, cardiac parasitic load, and inflammatory infiltrates. In addition, the treated mice had an increased survival rate. Taken together, these results indicate memantine to be a candidate drug for the treatment of Chagas disease.